High Readmission Rates and Mental Distress 1 yr After Ablation for Atrial Fibrillation or Atrial Flutter: A NATIONWIDE SURVEY. Issue 1 (January 2019) - Risom, Signe Stelling; Zwisler, Ann-Dorthe; Thygesen, Lau Caspar; Svendsen, Jesper Hastrup; Berg, Selina Kikkenborg
Abstract : Purpose: Today, catheter ablation is a widely used treatment for atrial fibrillation (AF) and atrial flutter (AFL). Knowledge on long-term patient-reported outcomes and readmissions is lacking and is warranted to plan optimal follow-up care. Objectives were to describe patient-reported outcomes including perceived health, quality of life, anxiety, depression, and physical activity compared with an age- and sex-matched reference population without longstanding disease; readmissions and mortality; and factors associated with suboptimal patient-reported outcomes. Methods: A nationwide cross-sectional survey mailed to 627 adults 6 to 12 mo after ablation for AF or AFL including; Short Form-36 (SF-36), HeartQoL, Hospital Anxiety Depression Scale, and questions about physical activity. Readmission rates and mortality were obtained and regression analyses were performed. Results: Comparing the patient group (response rate: 74%, n = 462) with an age- and sex-matched reference population with no long-lasting disease, differences were found in all subscales of SF-36 and leisure-time physical activity in favor of the reference group ( P < .001). Within 1 yr, 411 patients (59%) were readmitted and the total number of readmissions was 1167. Altogether, 227 (33%) patients were electively readmitted and 330 (48%) were acutely readmitted. Ten patients (1.4%) died. Age > 59 yr, female sex, high comorbidity, and readmission were associated with low physical health, low perceived health, and low quality of life. Conclusions: Patients treated for AF or AFL experienced decreased mental and physical health and high readmission rates 6 to 12 mo following catheter ablation. Closer multidisciplinary follow-up or cardiac rehabilitation after ablation for AF or AFL may be needed. Abstract : Knowledge on long-term patient-reported outcomes and readmissions is lacking among patients treated for atrial fibrillation or atrial flutter with catheter ablation. A nationwide cross-sectional survey with register follow-up and control group was conducted. Patients experienced decreased mental and physical health and high readmission rates. Multidisciplinary cardiac rehabilitation may be considered.